2009
DOI: 10.1002/ase.97
|View full text |Cite
|
Sign up to set email alerts
|

Clinical competencies and the basic sciences: An online case tutorial paradigm for delivery of integrated clinical and basic science content

Abstract: Understanding the relevance of basic science knowledge in the determination of patient assessment, diagnosis, and treatment is critical to good medical practice. One method often used to direct students in the fundamental process of integrating basic science and clinical information is problem-based learning (PBL). The faculty facilitated small group discussion format traditionally used for PBL is a significant challenge for faculty and facilities with a large class. To provide inductive learning to a large cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 20 publications
0
27
0
Order By: Relevance
“…This method uses different techniques, e.g. : classical clinical PBL, clinical cases for medical students based on computed tomography scans, real patient clinical cases based on real patients' problems or documented case presentation of the tutorials in the form of patient/physician history taking and physical examination videos [11,14,15,46,49]. However, the interactive lectures seem to be the most sophisticated variants of the PBL method during which small-group tutorial sessions are integrated into each anatomical section and use anatomical models, bones, radiographs, and interactive 3-dimensional (3D) images [18].…”
Section: Category 3 Other (Problem-based Learning and Visualisation)mentioning
confidence: 99%
“…This method uses different techniques, e.g. : classical clinical PBL, clinical cases for medical students based on computed tomography scans, real patient clinical cases based on real patients' problems or documented case presentation of the tutorials in the form of patient/physician history taking and physical examination videos [11,14,15,46,49]. However, the interactive lectures seem to be the most sophisticated variants of the PBL method during which small-group tutorial sessions are integrated into each anatomical section and use anatomical models, bones, radiographs, and interactive 3-dimensional (3D) images [18].…”
Section: Category 3 Other (Problem-based Learning and Visualisation)mentioning
confidence: 99%
“…to the learning platforms [13,[18][19][20][21][22][23]. Of these, three studies only recorded connections to the platform or folder and not the specific learning items contained within [18,19,21].…”
Section: Learning Analytics Data Typesmentioning
confidence: 99%
“…handouts, book chapters, journal articles, slides) [12,18,[20][21][22][23][26][27][28][29], onlinetests/quizzes [20,22,23,26,[29][30][31][32][33], and URL links to external online resources [20,22,23,29].…”
Section: Figure 1 Flowchart Of Search Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies measuring the use of videos prior to classes have shown mixed results. Numbers have varied between 39 % (DiLullo et al, 2009) to 70 % (Saxena et al) of students using the videos to prepare for class. Choi-Lunberg et al (2016a) found that while only 28 % of the students in their study accessed the video before their dissection class, 50 % of the students had watched all the videos by the end of semester, with the total viewings of videos jumping approximately 20 % in the last week before the exam.…”
Section: Utilisation Of Anatomy Videosmentioning
confidence: 99%